Crack growth analysis in welded and non-welded T-joints based on lock-in digital image correlation and thermoelastic stress analysis. (May 2018) - Chen, Daoyun; Sun, Shouguang; Dulieu-Barton, J.M.; Li, Qiang; Wang, Wenjing
Highlights: The method based on DIC and TSA is proposed to monitor crack propagation. The lock-in amplifier is used to process DIC speckle pattern images. Both the crack lengths and the stress intensity factors are evaluated. The tests on non-welded and welded specimens in two test rigs are compared. All of the results are validated by employing extended finite element method. Abstract: The method based on the digital image correlation (DIC) technique and thermoelastic stress analysis (TSA) is proposed to monitor the crack propagation process of T-joint specimens during the fatigue test. The lock-in amplifier is used to process DIC speckle pattern images while the specimen is dynamically loaded. The lock-in algorithm uses the fact that lock-in amplifier can be able to detect very small signal change within the measurement noise, which is often used in TSA. Using appropriate post-processing method, both the crack lengths and the stress intensity factors (SIF) can be evaluated in function of the number of fatigue cycles. The tests on non-welded T-joint specimens and welded T-joint specimens in two types of test rigs will be presented in the paper. All of the achieved results were validated by employing extended finite element method (XFEM) performed with ANSYS software.